Analisis kemampuan berpikir kreatif matematis siswa ditinjau dari kemampuan pemecahan masalah aritmatika sosial - Lailiyah, Nasyiatul; Prayito, Muhammad; Happy, Nurina (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
This study aims to determine the level of students mathematical creative thinking skills in terms of problem solving abilities of class VII students of SMP N 2 Bantarsari on social arithmetic material. This research is a qualitative descriptive study. The subjects of this study were seventh grade students of SMP N 2 Bantarsari which consisted of six students. Subject selection criteria were based on mathematical problem solving abilities, namely high, medium and low problem solving abilities. The instruments used in this research are problem solving ability test, mathematical creative thinking ability test and interview guide. The instrument has been validated by an expert before being used to determine whether the instrument is appropriate or not. The validity of the data using triangulation of sources, namely comparing the results of information obtained through different sources. The results obtained are 1) students with high problem solving skills in social arithmetic material are able to achieve creative thinking skills at level 4 which is very creative. 2) students with moderate problem-solving skills on social arithmetic material are able to achieve creative thinking skills at level 3, namely creative. 3) students with problem solving skills on low social arithmetic material who are able to show two indicators of mathematical creative thinking skills, namely in the aspects of fluent thinking and flexibility incluiding the ability to think creatively at level 2 which is quite creative. 4) students with problem solving skills on low social arithmetic material who are only able to show aspects of authenticity incluiding the ability to think creatively at level 1, which is not creative.